Evaluating Human and Financial Resources in Table Tennis from the workers point of View - Sabah, Wafaa (Journal of Physical Education, 2019)
The importance of the research lies in analyzing and following up the level of human Iraqi table tennis federation members' performance. The problem of the research lies in answering the following question; is the financial and human resources administration qualified and efficient in achieving the aims of the federation?The researchers used the descriptive method. The subjects were (201). The data was collected and treated using proper statistical methods. The results showed the efficiency of the scale to measure human and financial resources administration level of the Iraqi table tennis federation. The results also showed that the level of administration is disappointing.The researchers recommended encouraging work and development through participation in courses and developmental conferences inside and outside Iraq. Finally they recommended dedicating good financial resource for workers in the federation